Nitro BlueTetrazolium Chloride and Phagocytic Activity for Entamoeba Histolytica - Zaid Habeeb Abd-Alkareem; Jaber Hameed Hussain; Huda Jaber Waheed (College of Pharmacy / Mustansiriyah University, 2019)
Background: The NBT consist from two tetrazole molecules consider as the oxidative substance. The quantitative NBT test under standard conditions the leucocyte readiness is brooded together with NBT under standard conditions and declining of the color quantitated after extraction into pyridine is exceptionally valuable in the analysis by Spectro- photometry Entamoeba histolytica parasite induces apoptosis in host cells by for step(first)adherence to the host cell surface, (second) contact-subordinate cell killing, (third) start of phagocytosis so NBT used to determine percentage of phagocytosis for Entamoeba. Methods: This study was performed on 80 male they were divided to 25 control subjects and 55 subjects were diagnosed to be infected by Entamoeba histolytica at urban and rural areas in wassit   province. Entamoeba histolytica and   NBT were evaluated. Results: The results showed a significant difference between the two groups (10.96±2.745) for control group and 19.63±3.617 in patients' group with confidence interval (7.056-10.29). P.value P<0.001 ratio minimum number was 7%, 13% for the control and patient groups. Conclusion: There were a significant increase in phagocytic activity of polymorph neaucler neutrophils (PMNs) for reduction of NBT stain